Quantification of internal dosimetry in PET patients II: Individualized Monte Carlo‐based dosimetry for [18F]fluorocholine PET. Issue 9 (29th July 2021) - Neira, Sara; Guiu‐Souto, Jacobo; Pais, Paulino; Rodríguez Martínez de Llano, Sofía; Fernández, Carlos; Pubul, Virginia; Ruibal, Álvaro; Pombar, Miguel; Gago‐Arias, Araceli; Pardo‐Montero, Juan
Abstract: Purpose: To obtain individualized internal doses with a Monte Carlo (MC) method in patients undergoing diagnostic [18F]FCH‐PET studies and to compare such doses with the MIRD method calculations. Methods: A patient cohort of 17 males were imaged after intravenous administration of a mean [18F]FCH activity of 244.3 MBq. The resulting PET/CT images were processed in order to generate individualized input source and geometry files for dose computation with the MC tool GATE. The resulting dose estimates were studied and compared to the MIRD method with two different computational phantoms. Mass correction of the S‐factors was applied when possible. Potential sources of uncertainty were closely examined: the effect of partial body images, urinary bladder emptying, and biokinetic modeling. Results: Large differences in doses between our methodology and the MIRD method were found, generally in the range ±25%, and up to ±120% for some cases. The mass scaling showed improvements, especially for non‐walled and high‐uptake tissues. Simulations of the urinary bladder emptying showed negligible effects on doses to other organs, with the exception of the prostate. Dosimetry based on partial PET/CT images (excluding the legs) resulted in an overestimation of mean doses to bone, skin, and remaining tissues, and minor differences in other organs/tissues. Estimated uncertainties associated with the biokinetics of FCH introduce variations of cumulated activities in the range of ±10% in the high‐uptake organs. Conclusions: The MC methodology allows for a higher degree of dosimetry individualization than the MIRD methodology, which in some cases leads to important differences in dose values. Dosimetry of FCH‐PET based on a single partial PET study seems viable due to the particular biokinetics of FCH, even though some correction factors may need to be applied to estimate mean skin/bone doses.